(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study examines the accelerating shift from traditional human resource management (HRM) to Employee Experience Engineering (EXE) within Iraqi classified hotels, reconceptualizing the employee as an "internal customer" for whom an integrated work experience is deliberately designed. The study identifies knowledge, skill, and application gaps impeding Iraqi hotels from adopting this paradigm, and analyzes the theoretical foundations underpinning the Employee-as-Internal-Customer theory: the Service-Profit Chain (Heskett et al., 1994), Social Exchange Theory (Cropanzano & Mitchell, 2005), and Conservation of Resources Theory (Hobfoll, 2001). The research population comprises employees of three-to-five-star hotels across major Iraqi cities; a stratified random sample of 280 respondents from three tiers — front-line staff, HR managers, and executives — was employed. A descriptive-analytical-synthetic methodology grounded in a Systematic Literature Review (2011–2024) was adopted. Findings confirm that successful transformation requires leadership commitment, People Analytics infrastructure, and design-thinking training. The study’s original contribution is the TACT-EX Model — a five-phase framework (Transformation–Alignment–Culture–Technology–Experience) — which introduces the Arab Cultural Context (ACC) as a novel moderating variable absent from Western counterparts.